A New Species of Seed-harvester Ant, Pogonomyrmex hoelldobleri (Hymenoptera: Formicidae), from the Mohave and Sonoran Deserts of North America - Johnson, Robert A.; Overson, Rick P.; Moreau, Corrie S. (Zootaxa, 2013)
Pogonomyrmex magnacanthus Cole was described as a distinct species; unusually large eyes and a high ocular index (maximum eye diameter/head width) were listed as diagnostic characters. However, examination of numerous series of P. magnacanthus revealed that both characters were highly variable, and that these series consisted of P. magnacanthus plus an undescribed species, Pogonomyrmex hoelldobleri Johnson, Overson & Moreau sp. nov. This paper describes all three castes of P. hoelldobleri as well as the alate queen of P. mohavensis, which is very similar to that of P. hoelldobleri. A molecular phylogeny that consisted of 3,703 bp from one mitochondrial and five nuclear gene fragments supported the monophyly of P. hoelldobleri, P. magnacanthus, and P. mohavensis. Pogonomyrmex magnacanthus can be separated from other P. californicus group species based on: (1) its unusually large eyes, (2) a high ocular index, and (3) a malar ratio that is typically < 1.0. Pogonomyrmex hoelldobleri can be separated from other P. californicus group species based on the combination of: (1) eyes not unusually large, (2) cephalic rugae not forming circumocular whorls, but rather converging posterior to the eyes, usually near the vertex, (3) mandible with seven teeth, and (4) interrugal spaces on pronotal sides moderately to strongly granulate, dull to weakly shining. Pogonomyrmex mohavensis can be separated from other P. californicus group species based on the combination of: (1) eyes not unusually large, (2) cephalic rugae not forming circum-ocular whorls, but rather extending more or less directly to the vertex or converging only slightly near the vertex, (3) mandible with six teeth (a seventh sometimes occurs as a denticle between the basal and sub-basal teeth), and (4) interrugal spaces on pronotal sides smooth and shining to weakly punctate and moderately shining. We also provide field observations and distribution maps for P. magnacanthus, P. hoelldobleri, and P. mohavensis, and an updated key to P. californicus group species that occur in central and western North America.